SISTEM PENGENDALIAN SUHU HOTEND PADA PEMBUAT FILAMEN PET BERBAHAN BOTOL BEKAS - Taftazani, Moch. Aden; Rusli, Moch.; Muttaqin, Adharul (Jurnal Mahasiswa TEUB, 2024)
Indonesia, as the fourth most populous country in the world, faces serious challenges related to the issue of plastic waste. With a total population reaching 273.8 million in 2021, Indonesia is declared as the world's second largest contributor to plastic waste after China. Every year, approximately 3.2 million tons of plastic waste are poorly managed, with much of it ending up in the ocean. This is exacerbated by the low percentage of plastic waste recycling in Indonesia, which is less than 5%. One of the most common types of plastic waste is plastic bottles, particularly those made of Polyethylene Terephthalate (PET). It is estimated that over 580 billion PET bottles were produced and consumed worldwide in 2021. Recognizing this, plastic waste, especially PET bottles, becomes a promising recycling target. Therefore, a PET filament maker machine made from recycled bottles was designed. This research focuses on designing a temperature control system for the hotend of the filament maker machine using recycled bottles. In this study, a PID controller was used with parameter determination using the Ziegler-Nichols method, specifically the first method known as the reaction curve method. The test results indicate that the temperature control system can function effectively in maintaining the system response according to the desired setpoint values, with PID controller parameter values of Kp = 27.51, Ki = 1.06, and Kd = 178.8. The system response has a settling time of 2,350 seconds, a steady-state error of 0.2%, an overshoot of 12.74%, and a recovery time of 71 seconds when subjected to disturbances. Keywords: temperature control, filament maker, PET, PID controller, Ziegler-Nichols